National and Regional Covid-19 Pandemic Countermeasure Integration Policy - Sularto RB (EDP Sciences, 2021)
T1he Covid-19 virus pandemic has resulted in a fairly large scale of sufferers and deaths. For more than a year, Covid-19 Pandemic in Indonesia has killed more than 45,000 people. In order to prevent the spread of Covid-19 virus, it surely requires public policies issued at the national and regional levels. Through a normative research approach and covered by the Post-Positivism paradigm, it shows that public policies issued nationally and regionally are needed in synergy and integration to be able to regulate and determine so that citizens become obedient and together overcome the Covid-19 Virus Pandemic. There are two ways to deal with the Covid-19 virus, namely by using penal and using non-penal facilities. Both facilities are carried out together so that they are integrative and provide maximum results.